Anaemia in a South African colorectal ERAS programme – identifying the prevalence and predictors of preoperative anaemia and the effect on post-operative complications and length of stay - Nieuwenhuis, Kathryn (Department of Anaesthesia and Perioperative Medicine, 2023)
Background: Anaemia is a widespread public health problem associated with increased mortality and morbidity. In a surgical population, the prevalence of preoperative anaemia often exceeds that of the general population. Elective colorectal patients often have multiple risk factors for preoperative anaemia. The fourth updated ERAS Society guidelines for optimal perioperative care in colorectal surgery include specific recommendations for screening and treatment of preoperative anaemia as well as utilising restrictive blood transfusion practice. Assessing the prevalence and predictors of anaemia and outcomes in this population may allow for improved preoperative assessment and treatment of colorectal patients in a resource limited setting. Objectives: The primary objective of this retrospective study was to determine the prevalence of anaemia in the colorectal surgical population who were part of the enhanced recovery after surgery (ERAS) programme at a tertiary level hospital in the Western Cape, South Africa. Secondary objectives were to determine independent risk factors of preoperative anaemia, and the effect of anaemia on post-operative complications and length of stay after elective colorectal surgery. Methods: We performed a secondary analysis of data collected for the colorectal surgical ERAS programme. Data of 260 patients was reviewed from the initiation of the database 01 September 2016 to 30 September 2019. Three regression analyses were performed as part of the secondary objective to determine the risk factors for preoperative anaemia and predictors for postoperative complications and length of hospital stay. Patients were defined as anaemic if their haemoglobin was less than 13.0 g/dL. Results: The prevalence of preoperative anaemia was 157/260 (60.3%). Female sex (odds ratio (OR) 2.44, 95% confidence interval (CI) 1.43 – 4.18; p=0.001) and the presence of malignancy (OR 2.42, CI 1.26- 4.67; p=0.008) showed a significant association with anaemia. Anaemia was not associated with increased risk of post-operative complications or length of hospital stay. Conclusion: South African colorectal surgical patients in an enhanced recovery after surgery programme have a higher prevalence of preoperative anaemia compared to the general surgical population. Predictors of preoperative anaemia in this population included female sex and the presence of malignancy. Long waiting lists for patients awaiting elective colorectal surgery allow time for evaluation and optimisation of patients at risk for anaemia preoperatively